2011
DOI: 10.1002/jso.21903
|View full text |Cite
|
Sign up to set email alerts
|

Does metastasectomy improve survival in patients with stage IV melanoma? a cancer registry analysis of outcomes

Abstract: Introduction Patients with Stage IV melanoma have limited therapeutic options with few long term survivors. Our goal was to study the impact of metastasectomy on survival in these patients. Methods Patients with Stage IV melanoma were identified from the Surveillance, Epidemiology and End Results (SEER) database (1988–2006). Those who had metastasectomy performed were compared with patients that did not. Results The median age of the study population (n= 4229) was 63 years and median survival was 7 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 26 publications
1
61
0
2
Order By: Relevance
“…Several studies have demonstrated that metastasectomy can significantly improve survival in selected patients, achieving a five-year survival rate of 11-49% for M1a stage, 5-31% for M1b and 7-28% for M1c. [15][16][17][18][19] Different theories have been advanced as explanation of these findings. One of them is that a reduction of tumor burden leads to a more efficiently function of the host's immune system.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that metastasectomy can significantly improve survival in selected patients, achieving a five-year survival rate of 11-49% for M1a stage, 5-31% for M1b and 7-28% for M1c. [15][16][17][18][19] Different theories have been advanced as explanation of these findings. One of them is that a reduction of tumor burden leads to a more efficiently function of the host's immune system.…”
mentioning
confidence: 99%
“…Меланома кожи, включающая метастазы в кожу, мяг-кие ткани и не регионарные лимфоузлы, занимает около 40% от пациентов с IV стадией заболевания (M1a). У дан-ной категории пациентов медиана выживаемости после успешного хирургического лечения составляет 40 меся-цев (по сравнению с 6 месяцами у пациентов без удале-ния метастазов [10]), что полностью оправдывает хирур-гическую тактику лечения у данной категории пациентов. Операция должна быть выполнена на начальном этапе диссеминации, то есть при отсутствии множественных метастазов в кожу и распространения метастазов на не-сколько групп лимфатических узлов.…”
Section: анализ применения хирургического лечения отдаленных метастазunclassified
“…По данным Surveillance, Epidemiology and End Results (SEER) (1988-2006 г. ), из 4 229 пациентов с IV стадией меланомы кожи 33,6% пациентов перенесли удаление ме-тастазов и имели лучшую медиану выживаемости и 5-лет-нюю выживаемость по сравнению с пациентами, получив-шими только консервативное лечение (12 месяцев против 5 месяцев и 16% против 7% соответственно) [14]. Вышеприведенные данные кажутся весьма оптимистиче-скими, так как медиана и 5-летняя выживаемость пациен-тов, перенесших хирургическое лечение метастазов, пре-вышает данные показатели при консервативном лечении практически в 2 раза.…”
Section: анализ применения хирургического лечения отдаленных метастазunclassified
“…If complete resection of all metastatic disease is possible, patients should consider metastasectomy as first-line treatment; this is supported by level B retrospective outcome studies, especially when a solitary metastasis is present (Figure 3). [34][35][36][37] Following immunotherapy, patients who achieve partial or stable disease responses should be re-assessed for resection. 38,39 The panel recognizes several systemic treatment options for unresectable stage IV melanoma, including high-dose IL-2 (where available), ipilimumab, vemurafenib, dabrafenib and trametinib for patients with BRAF mutated tumours, clinical trial p articipation and cytotoxic chemotherapy.…”
Section: Initial Assessmentmentioning
confidence: 99%